A study on the outreach programs of selected private academic libraries in Metro Manila - Casimiro, Noel Salvador B. (2012)
Since librarianship is a profession based on service, it is crucial to identify and describe activities that promote and put into action the notion of service. An example of this activity is library outreach where librarians are conducting information and other services outside the confines of their library. This study concentrated on the outreach programs of six selected private academic libraries in Metro Manila namely: Ateneo de Manila University Rizal Library, Far Eastern University Library, Lyceum of the Philippines University Sotero H. Laurel Academic Resources Center, University of the East-Manila Library, The University of Manila Library, and the University of Santo Tomas Miguel de Benavides Library.